2021
DOI: 10.1149/1945-7111/ac35cf
|View full text |Cite
|
Sign up to set email alerts
|

Ionically Crosslinked Composite Membranes from Polybenzimidazole and Sulfonated Poly (fluorenyl ether ketone) for High-Temperature PEM Fuel Cells

Abstract: A series of composite polymer membranes composed of poly [2,2″-(p-oxydiphenylene)-5,5″-benzimidazole] (OPBI) and sulfonated poly (fluorenyl ether ketone) (SPFEK) were developed with enhanced mechanical integrity and superior oxidative stability. The phosphonic acid (PA) doped OPBI-SPFEK membranes were then fabricated for the high temperature-proton exchange membrane fuel cells (HT-PEMFCs) application. It is suggested that an ionically crosslinked structure can be formed by the intense interaction among the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 36 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…Over the last few years, different types of sulfonated aromatic polymer materials, including sulfonated polyarylene ether sulfone (SPAES), 31,32 sulfonated polyimide (SPI), 33 sulfonated polybenzimidazole (SPBI), 34,35 sulfonated polyether ether ketone (SPEEK), 36 sulfonated poly(fluorenyl ether ketone) (SPFEK), 37 and sulfonated polyether sulfone (SPES), 38 have been developed and applied in HT-PEMs due to their remarkable structural stability and mechanical strength. For instance, Ye et al 39 reported noncovalent cross-linked membranes using one uracil-terminated telechelic sulfonated polyimide (SPI-U) and another adenine-based crosslinking agent (SMA-A) to form bio-complementary hydrogen bonding, and the modified composite membranes presented improved proton conductivity and more optimal antioxidant performance.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last few years, different types of sulfonated aromatic polymer materials, including sulfonated polyarylene ether sulfone (SPAES), 31,32 sulfonated polyimide (SPI), 33 sulfonated polybenzimidazole (SPBI), 34,35 sulfonated polyether ether ketone (SPEEK), 36 sulfonated poly(fluorenyl ether ketone) (SPFEK), 37 and sulfonated polyether sulfone (SPES), 38 have been developed and applied in HT-PEMs due to their remarkable structural stability and mechanical strength. For instance, Ye et al 39 reported noncovalent cross-linked membranes using one uracil-terminated telechelic sulfonated polyimide (SPI-U) and another adenine-based crosslinking agent (SMA-A) to form bio-complementary hydrogen bonding, and the modified composite membranes presented improved proton conductivity and more optimal antioxidant performance.…”
Section: Introductionmentioning
confidence: 99%